2021
DOI: 10.1016/j.ajogmf.2021.100390
|View full text |Cite
|
Sign up to set email alerts
|

The impact of peak and duration of maternal intrapartum fever on perinatal outcomes

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Hochler et al found that maximal parturient temperature, solely and in combination with fever duration, had a dose–response effect on adverse neonatal outcomes while duration alone was not significantly correlated with maternal and neonatal outcomes, 10 which was partly in accordance with our findings. They suggested in case with a higher peak temperature, effort should be made to avoid long labor to minimize fetal exposure and harm, 10 however, the appropriate duration of fever was not suggested. For women with different fever peak, their encouraged time of labor may be different to reduce neonatal morbidity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hochler et al found that maximal parturient temperature, solely and in combination with fever duration, had a dose–response effect on adverse neonatal outcomes while duration alone was not significantly correlated with maternal and neonatal outcomes, 10 which was partly in accordance with our findings. They suggested in case with a higher peak temperature, effort should be made to avoid long labor to minimize fetal exposure and harm, 10 however, the appropriate duration of fever was not suggested. For women with different fever peak, their encouraged time of labor may be different to reduce neonatal morbidity.…”
Section: Discussionsupporting
confidence: 92%
“…19 Ashwal et al found that the risk for adverse perinatal outcomes was also related to intrapartum fever duration, but the relationship between peak temperature and adverse neonatal outcomes was not investgated. 11 Hochler et al found that maximal parturient temperature, solely and in combination with fever duration, had a doseresponse effect on adverse neonatal outcomes while duration alone was not significantly correlated with maternal and neonatal outcomes, 10 which was partly in accordance with our findings. They suggested in case with a higher peak temperature, effort should be made to avoid long labor to minimize fetal exposure and harm, 10 however, the appropriate duration of fever was not suggested.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There is increasing evidence that most intrapartum fevers arise from non-infectious etiologies, notably epidural analgesia ( Riley et al, 2011 ; Hochler et al, 2021 ). Nonetheless, notwithstanding its cause, intrapartum fever is linked to severe maternal, as well as neonatal outcomes ( Hochler et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that most intrapartum fevers arise from non-infectious etiologies, notably epidural analgesia ( Riley et al, 2011 ; Hochler et al, 2021 ). Nonetheless, notwithstanding its cause, intrapartum fever is linked to severe maternal, as well as neonatal outcomes ( Hochler et al, 2021 ). However, in some investigations, there was no remarkable link between intrapartum fever and long-term adverse events in offspring ( Towers et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%